The development of non-linear knowledge: New risks, vulnerabilities, and hopes - Kravchenko, S.A. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2018)
The article considers the non-linear knowledge as the result of the ‘arrow of time’ effect (I. Prigogine) that determined the new realities in which everything develops increasingly quicker and in a more complex way. The author extends the impact of this effect to the dynamics of knowledge and shows that the modern knowledge acquires the quality of reflexivity and takes on a completely new vector of non-linear development within the so-called ‘turns’ in the history of science. The transition from linear to non-linear knowledge determines more complex manufactured risks including the threat of dehumanization described in the article. The monitoring of these risks implies that the value-oriented non-linear knowledge should be taken into account not only by natural, technical and social sciences but also by the humanities. Among new challenges to the humanity there are vulnerabilities manifested in the increasing structural dysfunctions of complex social and/or techno-natural systems in the form of ‘normal accidents’, ‘collateral damage’, etc. The author believes that key challenges of such vulnerabilities are determined by the dominant pragmatic values of modern knowledge. There is also a new type of development in the form of metamorphosis leading to non-linear transformations, which aggravates the complex character of modern risks and vulnerabilities. The author finds answers to these challenges in the humanistic turn that can ensure the valid knowledge of complex risks and vulnerabilities together with the grounds for better future that people want.